Effect of cytogenetic risk status on outcomes for patients with acute myeloid leukemia undergoing various types of allogeneic hematopoietic cell transplantation: an analysis of 7812 patients. Issue 3 (4th March 2018) - Yanada, Masamitsu; Mori, Jinichi; Aoki, Jun; Harada, Kaito; Mizuno, Shohei; Uchida, Naoyuki; Kurosawa, Saiko; Toya, Takashi; Kanamori, Heiwa; Ozawa, Yukiyasu; Ogawa, Hiroyasu; Henzan, Hideho; et al.
Abstract: This study aimed at determining how cytogenetic risk status affects outcomes for patients with acute myeloid leukemia (AML) after undergoing various types of allogeneic hematopoietic cell transplantation (HCT). Of 7812 patients eligible for analysis, cytogenetic risk was classified as favorable for 1088, intermediate for 5025, and poor for 1699. Overall, multivariate analysis showed significant intergroup differences in terms of relapse and survival, with the difference between poor- and intermediate-risk groups being greater than that between favorable- and intermediate-risk groups. Non-relapse mortality was identical for the three groups. Significant effects of cytogenetic risk status on survival were documented irrespective of donor type (related, unrelated, and umbilical cord blood), disease status at the time of transplantation (first or second complete remission, and more advanced disease status), and conditioning intensity (myeloablative and reduced-intensity). Our findings demonstrate robust and constant effects of cytogenetic risk status on survival after allogeneic HCT for patients with AML.